2011
DOI: 10.1007/s11249-011-9856-9
|View full text |Cite
|
Sign up to set email alerts
|

Friction Measurements on Contact Lenses in Their Operating Environment

Abstract: An important issue concerning the use of soft contact lenses is comfort, which, among other factors, has been related to the level of friction between the anterior side of the lens and the inner eyelid. Although several studies have been carried out to investigate the frictional properties of contact lenses, these have not taken the physiological environment of the eye into account. In use, lenses are in contact with proteins present in tears, with corneal cells and with the palpebral conjunctiva (clear membra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
122
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(130 citation statements)
references
References 17 publications
8
122
0
Order By: Relevance
“…Although the experimental conditions (e.g. counterbody geometry, normal load, sliding velocity) vary from study to study, the values obtained are of the same order of magnitude of those previously published for similar hydrogels: Yanez et al [34] reported analogous values for pHEMA hydrogels containing PVP, and Roba et al [28] also found comparable values for various commercial contact lenses.…”
Section: Characterization Of the Hydrogelssupporting
confidence: 74%
See 1 more Smart Citation
“…Although the experimental conditions (e.g. counterbody geometry, normal load, sliding velocity) vary from study to study, the values obtained are of the same order of magnitude of those previously published for similar hydrogels: Yanez et al [34] reported analogous values for pHEMA hydrogels containing PVP, and Roba et al [28] also found comparable values for various commercial contact lenses.…”
Section: Characterization Of the Hydrogelssupporting
confidence: 74%
“…PVP increases the hydrophilicity of the material and has self-lubricant properties essential to the comfort and good performance of the contact lenses [27,28]. One hydrogel was prepared using an anhydrous mixture.…”
mentioning
confidence: 99%
“…Although CLs are widespread, a significant fraction of people are unable to wear them due to discomfort and ocular irritation. These symptoms are generally associated with physiological problems, such as the dry eye syndrome, and/or to proteins/lipids adsorption and friction between the eyelid and the anterior surface of the lens [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Roba et al [18] state that this may lead to misleading results and concluded about the relevance of mimicking the eye's physiological environment, not only in what concerns parameters like the normal load and velocity, but also the lubricant solution composition. They suggest the use of a lubricant based on the packaging solution, containing lysozyme and serum, but without lipids.…”
Section: Introductionmentioning
confidence: 99%
“…Contact lens wearers in particular experience ocular discomfort and this is one of the primary reasons for ceasing lens wear 3 . When a contact lens is placed on the eye, the friction coefficient between the lens material and the ocular surface has been shown to change 4 . There is evidence to suggest that dryness symptoms could be related to this altered friction 2,5,6 .…”
Section: Introductionmentioning
confidence: 99%